Insertion sequences in mgrB and mutations in two-component system genes confer high polymyxin resistance to carbapenem-resistant Enterobacter cloacae complex strains - Wu, Jiming; Zhang, Jisheng; Wang, Jianmin; Wang, Jin; Liang, Xushan; Wei, Chunli; Long, Wenzhang; Yang, Yang; Chen, Yuhui; Liao, Mingjing; Liang, Youtao; Yu, Kaixin; et al. (Frontiers in Microbiology, 2025)
Due to the complexity of identifying the Enterobacter cloacae complex (ECC) at the species level, little is known about the distribution of carbapenem-resistant ECC (CRECC). Plasmid-mediated mcr family genes are significant contributors to polymyxin resistance. The emergence of the mcr-9 gene has further complicated the landscape of polymyxin resistance in CRECC. Our study aimed to ascertain the prevalence of CRECC and the mcr-9 gene, and to elucidate the mechanisms underlying high-level resistance to polymyxin B (PB). In this study, we collected 212 non-replicating ECC strains, identifying 38 CRECC strains (17.9%, 38/212) and Enterobacter hormaechei (71.1%, 27/38) as the predominant endemic strains. Among these, 10 CRECC strains (36.3%, 10/38) were found to harbor the mcr-9 gene. Interestingly, the presence of mcr-9 did not significantly impact PB resistance or impose a fitness cost. While overexpression of mcr-9 can enhance PB resistance within a certain range and may incur fitness costs, it does not result in high-level PB resistance. The PB resistance of 17 CRECC strains was notably increased (from 16 to 128 mg/L), accompanied by mutations in the phoP/Q and mgrB genes. Notably, two novel insertion sequences, IS5D and IS1X2, were discovered within the mgrB gene. The inactivation of mgrB results in the loss of its negative regulatory effect on the two-component system. Protein structure predictions indicated that mutations in phoQ primarily affect the phosphatase (HAMP) and histidine kinase domains. This research significantly expands our comprehension of the complexities of PB resistance, highlighting the multifactorial nature of antibiotic resistance mechanisms.